On q-statistical approximation of wavelets aided Kantorovich q-Baskakov operators - Ayman-Mursaleen, Mohammad; Lamichhane, Bishnu; Kiliçman, Adem; Senu, Norazak (National Library of Serbia, 2024)
The aim of this research is to examine various statistical approximation properties of Kantorovich q-Baskakov operators using wavelets. We discuss and investigate the weighted statistical approximation employing a Bohman-Korovkin type theorem as well as a statistical rate of convergence applying a weighted modulus of smoothness ωρα correlated with the space Bρα (R+) and Lipschitz type maximal functions.